HOW DO KNOWLEDGE AND SELF-EFFICACY OF INTERNSHIP NURSING STUDENTS IN PERFORMING CARDIOPULMONARY RESUSCITATION? - Selly Desiani; Aan Nuraeni; Ayu Prawesti Priambodo (Belitung Raya Foundation, 2017)
Background: Cardiopulmonary Resuscitation (CPR) is the emergency first aid in cardiac arrest. CPR delivery is influenced by knowledge and self-efficacy. Internship students can be the first responder of cardiac arrest in hospital and expected on having knowledge and high self-efficacy of CPR early. But there is no data on self-efficacy of internship students in performing CPR. Objective: The purpose of this research was to identify knowledge and self-efficacy of internship students in performing CPR. Methods: The method in this research was descriptive quantitative with cross-sectional approach on 76 internship students selected by simple random sampling. Knowledge questionnaire and Resuscitation Self-Efficacy Scale instrument were used in this research, with validity score 0.56-0.84 (α=0.91). Data were analysed by distribution frequency. Results: The results showed that 49 respondents (64.5%) had moderate knowledge and 73 respondents (96.1%) had high self-efficacy. The lowest domain in knowledge was conceptual knowledge, while in self-efficacy were reporting, debriefing and recording. Conclusions: Therefore, it becomes important to increase information on the conceptual knowledge and enhances training on the self-efficacy domain: reporting; debriefing and recording.